The Definition and Diagnosis of Complicated Appendicitis - Kumar H.R (Medical Science: Trends and Innovations Vol. 5, 2025)
The definition of complicated appendicitis has been an area of concern due to the absence of any universal consensus. Complicated appendicitis often means perforation of the appendix with either peritonitis, abscess, or mass formation. The diagnosis of complicated appendicitis is another area where there is no consensus and there is no one investigation that can diagnose this condition. Diagnosis often involves the use of clinical examinations, laboratory parameters, and imaging modalities. In this study, the definition and diagnosis of complicated appendicitis were discussed.